Vascular reactivity to various vasoconstrictor agents and endothelium-dependent relaxations of rat thoracic aorta in the long-term period of pinealectomy - Kurcer, Zehra; Sahna, Engin; Olmez, Ercument (Japanese Pharmacological Soc, 2006)
In this study, the effects of reduced melatonin concentrations in the long-term period of pinealectomy on mean arterial blood pressure (BP) and vascular responses in isolated rat thoracic aorta were investigated. Rats were pinealectomized (Px) two months before the beginning of the studies. Rings of endothelium-intact and -denuded rat arteries were mounted in isolated tissue baths for the measurements of isometric contractile force. No significant difference was determined between the arterial BP of Px (88.1 +/- 1.9 mmHg) and control (83.8 +/- 1.2 mmHg) rats. All arteries isolated from control and Px rats showed essentially identical contractions in response to phenylephrine, serotonin, calcium, clonidine, vasopressin, and angiotensin-II. Only endothelin-1 (ET-l)-induced contractions in the endothelium-denuded vessels isolated from Px rats were found to be increased to some extent. Pinealectomy did not affect acetylcholine or sodium nitroprusside-induced relaxation in the rat aorta either. These data suggest that reduced melatonin levels two months after pinealectomy did not modify either the vascular reactivity to various vasoconstrictor agents except the partially increased contractile responses to ET-I in the endothelium-denuded thoracic aortas of Px rats or the endothelium-dependent and -independent relaxations in rat thoracic aorta. Restoration of the increased vascular responses to some vasoconstrictor agents, which were reported previously, may be the reason of why the hypertension is temporary following pinealectomy.
Keywords: melatonin; pinealectomy; rat aorta; vascular reactivity